(untitled) (Research, Society and Development, 2021)
The aim of this study was to examine the effects of (-)-myrtenol alone and combined with antifungal agents against Candida spp. The Minimum Inhibitory Concentration (MIC) and Minimum Fungicidal Concentration of (-)-myrtenol and fluconazole against C. albicans and C. parapsilosis strains was obtained using CLSI guidelines. Combination of (-)-myrtenol with antifungal drugs was determined by checkboard test. The (-) myrtenol showed MIC ranging from 256 to 512 µg/mL against both species assay. And the MFC was 512 µg/mL, demonstrated nature fungicidal (MFC/MIC < 4). In addition, combination of antifungal agents (amphotericin B and fluconazole) and (-) myrtenol showed synergistic and additive effects on strains assays. Based on these results, the present study demonstrates that (-) myrtenol showed strong fungicide activity against Candida spp. In addition, Combination of antifungal agents and (-) myrtenol reduces the effective concentrations of both the agents with synergistic to additive effects. Therefore, (-) myrtenol has potential to be developed into an antifungal agent.